Emotional intelligence: the needs for emotional intelleigence among the non-executive workers of tabung haji Kuching branch from the perspective of customers - Noor Fazilah, Ahmad Jamli (Universiti Malaysia Sarawak (UNIMAS), 2004)
This survey was carried out to identify the needs for Emotional Intelligence among the non- executive workers of TAB UNG HAJJ KU CHING BRANCH in Kuching, Sarawak. The respondent consist of customers of TABUNG HAJI KU CHING BRANCH and data are acquired from all of the respondent (n = 100). In this research questionnaires are developed based on the element of Emotional Intelligence in five distinctive area which are Self -Awareness, Self- Regulation, Motivation, Empathy and Social Skills by Golemen, D. (1998) model. From this research, it is found that customers are satisfied with the EQ element of Social Skills, Empathy, Motivation and Self- Regulation among the non- executive workers of TABUNG HAJI KUCHING BRANCH. However, TABUNG HAJI have needs to put an effort to help the non- executive workers improve the element of Self -Awareness for the reason that it has low correlation with customer satisfaction.